Four new HLA class I alleles, HLA‐A*02:681, HLA‐A*30:111, HLA‐A*68:164 and HLA‐B*35:01:46. (14th June 2017) - Sánchez‐Gordo, F.; Balas, A.; Gomez‐Zumaquero, J. M.; Vicario, J. L.
Abstract : Four new HLA class I alleles, HLA‐A*02:681, HLA‐A*30:111, HLA‐A*68:164 and HLA‐B*35:01:46 were described in Spaniards.